Analysis of Income for Laying Hen Farming Business in Puncak Harapan Village, Enrekang Regency - Musnaim; Angga Nugraha; Musdalifah Mansur (MultiTech Publisher, 2023)
This research aims to determine the income of the laying hen farming business in Puncak Harapan Village, Enrekang Regency. The research population was 30 purebred chicken breeders and a sample of 30 respondents. The sampling technique in this research is in accordance with the statement of Gay and Diehl (1992. The data collection techniques applied in the research are observation, questionnaires or questionnaires. The results of the research can be concluded that the income of the laying hen farming business in Puncak Harapan Village is influenced by several factors such as chicken population, education and work experience. Livestock business income based on scale size is calculated by total revenue minus total costs equal to monthly profit or income. Total income for scale 1 farm with a population of 3000-5000 is IDR 94,850,000, scale 2 with a population of 5000-10,000 is IDR 123,695,000 and scale 3 with a population of 10,000-30,000 is IDR 291,045,000.